2011
DOI: 10.1159/000334162
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Management of Complete Androgen Insensitivity Syndrome from Adolescence Onward

Abstract: Complete androgen insensitivity syndrome (CAIS) represents a main disorder of sex development. Women with CAIS may have their gonads removed before, during or after adolescence, thus requiring hormonal replacement therapy to induce puberty and/or maintain secondary sexual characteristics, to optimize bone mass accrual, and to promote physical and social well-being. Usually estrogens are used for this purpose, but formulations and doses should be better defined in multicentric prospective studies. Some women st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…Our findings would also imply a different approach to HRT in those women with CAIS who underwent gonadectomy. E2 replacement therapy currently aims at much higher estradiol levels in the female reference range, whereas T substitution is not a common practice [Bertelloni et al, 2011]. Malcompliance with HRT due to impaired physical well-being may be related to unphysiological hormone profiles with such therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings would also imply a different approach to HRT in those women with CAIS who underwent gonadectomy. E2 replacement therapy currently aims at much higher estradiol levels in the female reference range, whereas T substitution is not a common practice [Bertelloni et al, 2011]. Malcompliance with HRT due to impaired physical well-being may be related to unphysiological hormone profiles with such therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent observations indicate that the risk of developing germ cell tumors before and during puberty is low in women with CAIS [Lecca et al, 1988;Cools et al, 2006;Hannema et al, 2006;Looijenga et al, 2007;Hersmus et al, 2008;Wünsch et al, 2012]. For those who underwent gonadectomy, hormone replacement therapy (HRT) is mandatory to induce puberty and improve bone health and well-being [Bertelloni et al, 2011].…”
mentioning
confidence: 99%
“…After gonadectomy, continuous and long-term hormone therapy is necessary to achieve induction of puberty and maintenance of sexual function, psychosocial well-being, and bone health [Bertelloni et al, 2011]. So far, there have not been any studies reported that examine different hormonal medications, their dosage, and routes of administration necessary to obtain these aims.…”
Section: The Dilemma Of Gonadectomymentioning
confidence: 99%
“…Based on these data, and in line with demands from advocacy groups to restrict surgery in DSD children wherever possible, many DSD centers gradually adopted a policy of postponing prophylactic gonadectomy to late adolescence in individuals with CAIS [Hughes et al, 2012]. Such an approach allows for spontaneous breast development and bone mass accrual during puberty through peripheral conversion of androgens to estrogens [Bertelloni et al, 2010[Bertelloni et al, , 2011 without compromising safety regarding tumor development. In addition, informed consent for gonadectomy can be obtained directly from the adolescent girl, alleviating the pressure on parents and promoting psychological adaptation in patients [Siminoff and Sandberg, 2015].…”
mentioning
confidence: 99%